Testes de modificações da gravitação na escala atômica - Luna, Gabriela Coutinho (2020)
There are some theoretical scenarios, as the large-scale extra dimensions models, that predict a strengthening of the gravitational field for short distances. Motivated by this, we investigate deviations of the gravitational field in the atomic length scale. Using recent data from hydrogen spectroscopy, we obtained new empirical limits for supposed modifications of the standard gravity on this scale. The new limits were extracted from the 1S − 3S transition frequency. We compared them with the spectroscopic data of the antiprotonic helium, which determine one of the most stringent bound for deviations of the Newtonian potential in this domain. We found that our results are slightly stronger that the antiprotonic helium limit. Other constraints were obtained from the analysis of the effect of gravitational spin-orbit coupling in atomic spectroscopy for the transition 2P1/2− 2P3/2. Such bounds are stronger than limits previously determined by an experiment that measures the electron spin precession in an electron-nucleus scattering. We also show that the analysis of this interaction, responsible for the spin precession, can be used as a test of Post-Newtonian potential in the atomic domain.